Cover Picture: Following Cu Microstructure Evolution in CuZnO/Al2O3(−Cs) Catalysts During Activation in H2 using in situ XRD and XRD‐CT (Chem. Methods 1/2023). Issue 1 (21st December 2022) - Farmer, Daniela M.; Jacques, Simon D. M.; Waller, David; Boullosa Eiras, Sara; Roy, Kanak; Held, Georg; Sankar, Gopinathan; Beale, Andrew M.
Abstract : The Front Cover shows how X‐rays can be used to obtain spatially resolved chemical imaging insight from within an industrial catalytic reactor. Understanding how the microstructure of the active Cu 0 component in the commercially applicable Cu/ZnO/Al2 O3 (−Cs2 O) low‐temperature water‐gas shift catalyst evolves under various H2 partial pressures in the presence/absence of a Cs promoter during thermal activation has been the subject of the present investigation. More information can be found in the Research Article by Daniela M. Farmer et al. .